THE ROLE AND SIGNIFICANCE OF INCORPORATION IN THE PROCESS OF SYSTEMATIZING LEGISLATION - Choriyev Ulug‘bek Rustamovich (European Science Publishing, 2025)
This article provides a detailed analysis of incorporation, one of the main forms of systematizing legislation. Incorporation is the process of combining existing normative legal acts into compilations without changing their content, and its specific features that distinguish it from codification are substantiated. The article discusses various types of incorporation, including official, unofficial, and semi-official forms, as well as modern electronic incorporation and their practical relevance. In particular, the electronic incorporation system in Uzbekistan is examined, along with its advantages and existing shortcomings, based on a social survey. The author also presents practical recommendations for improving the legislative systematization process.
Keywords: This article provides a detailed analysis of incorporation, one of the main forms of systematizing legislation. Incorporation is the process of combining existing normative legal acts into compilations without changing their content, and its specific features that distinguish it from codification are substantiated. The article discusses various types of incorporation, including official, unofficial, and semi-official forms, as well as modern electronic incorporation and their practical relevance. In particular, the electronic incorporation system in Uzbekistan is examined, along with its advantages and existing shortcomings, based on a social survey. The author also presents practical recommendations for improving the legislative systematization process.